If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 3 = 2 + -4m Reorder the terms: 3 + 5m = 2 + -4m Solving 3 + 5m = 2 + -4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4m' to each side of the equation. 3 + 5m + 4m = 2 + -4m + 4m Combine like terms: 5m + 4m = 9m 3 + 9m = 2 + -4m + 4m Combine like terms: -4m + 4m = 0 3 + 9m = 2 + 0 3 + 9m = 2 Add '-3' to each side of the equation. 3 + -3 + 9m = 2 + -3 Combine like terms: 3 + -3 = 0 0 + 9m = 2 + -3 9m = 2 + -3 Combine like terms: 2 + -3 = -1 9m = -1 Divide each side by '9'. m = -0.1111111111 Simplifying m = -0.1111111111
| 4x+23=x+20 | | 3/5x-9 | | 180=40x-21 | | 5x-35=-10 | | =(3x^3) | | 26x+20-6x^2=0 | | ((-2w^2)/u)^3 | | 26=1.1R+0.2R | | g(0)=-1/2 | | -8=3+s | | 0.6x+8.9=5.6 | | 6(y-8)+3=33 | | 18d+4d^2=10 | | -5(-6y+3)-7y=7(y-4)-1 | | 2w+46=-2(w-3) | | -1/2-3.5 | | 3a-16a+16=0 | | (4v-6)(5-V)=0 | | c^2-13c-30=0 | | 40=2L+2(8) | | y=-0.2x+4.2 | | 7amx-7c=4x+5y | | 38.76+e=227.5 | | 8y^3-6y-1=0 | | 4-(2-x)=-3(2x+6) | | 8y-(3-6y)=0 | | 4-3x=12x+9 | | x-.18=163.43 | | 7-4.3=8.5 | | 6x+5-3=2x-15 | | -9u^9v^19= | | 9x^2+4y^2=144 |